2014
DOI: 10.1542/peds.2013-2991
|View full text |Cite
|
Sign up to set email alerts
|

Sexting and Sexual Behavior Among Middle School Students

Abstract: OBJECTIVE: It is unknown if “sexting” (ie, sending/receiving sexually explicit cell phone text or picture messages) is associated with sexual activity and sexual risk behavior among early adolescents, as has been found for high school students. To date, no published data have examined these relationships exclusively among a probability sample of middle school students. METHODS: A probability sample of 1285 students was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 20 publications
(24 reference statements)
13
113
1
2
Order By: Relevance
“…The authors argue that sexting might serve as prelude or gateway behaviour to actual sexual behaviour, or as a way of indicating readiness to take intimacy to the next level. Temple and Choi (2014) did not find a relationship with sexual risk behaviour, contrary to the findings of other cross-sectional studies (Benotsch et al, 2013;Dake et al, 2012;Ferguson, 2010;Perkins et al, 2014;Rice et al, 2014) where sexting was associated with high-risk sexual behaviours (e.g. multiple partners and anal sex and unprotected sex).…”
Section: Associations With Sexual Behavioursmentioning
confidence: 69%
See 2 more Smart Citations
“…The authors argue that sexting might serve as prelude or gateway behaviour to actual sexual behaviour, or as a way of indicating readiness to take intimacy to the next level. Temple and Choi (2014) did not find a relationship with sexual risk behaviour, contrary to the findings of other cross-sectional studies (Benotsch et al, 2013;Dake et al, 2012;Ferguson, 2010;Perkins et al, 2014;Rice et al, 2014) where sexting was associated with high-risk sexual behaviours (e.g. multiple partners and anal sex and unprotected sex).…”
Section: Associations With Sexual Behavioursmentioning
confidence: 69%
“…Some researchers found similar rates of sexting for boys and girls (e.g. Dake, et al, 2012;Lenhart, 2009;Rice et al, 2014), while others found a higher frequency among boys (Dowdell, Burgess, & Flores, 2011) and vice versa National Campaign to Prevent Teen and Unplanned Pregnancy & CosmoGirl.com, 2008). Data from the EU Kids Online Project showed that in Sweden boys sent and posted sexual pictures slightly more than girls, 12.9% vs. 10.2% (Baumgartner et al, 2014), while the studies from Ungdomsstyrelsen (2009; indicated that girls posted sexual pictures more often than boys (6.2 % vs. 4.0%).…”
Section: Socio-demography and Psychosocial Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a recent study of younger adolescents (ages 10-15) finding boys more likely than girls to send sexually explicit messages or photos. 39 Finally, findings from this nonrepresentative sample from 8 SHCs in 1 Northern California region cannot be generalized to all high school-age students.…”
Section: Discussionmentioning
confidence: 87%
“…Sexting has been shown to be associated with other sexual activities. Sexters seem to be more sexually active (Rice et al, 2014;Sorbring et al, 2014) and became sexually active earlier in life (Perkins et al, 2014;Rice et al, 2014). However, sending sexual messages does not necessarily need to be associated with sex.…”
Section: Sexuality and The Online Culturementioning
confidence: 99%